Energy consumption and CO2 emissions in the northern cities (case of Yakutia) - Tuyara Gavrilyeva (European Regional Science Association (ERSA), 2016)
The huge territory and long distances between settlements (up to 700 km) determine the complex structure of the energy system of Yakutia. The average duration of the heating season in the region is 8-9 months, and 12 months in the Arctic. Electricity generation is carried out mostly by low-capacity boilers using coal and diesel fuel. About 85% of fuel is imported from outside of Yakutia. The northern provision is seasonal, due to a complicated transport scheme. The time of fuel delivery reaches 18 - 30 months. As a result, the net cost of electricity generation in the Arctic is higher than in Central Yakutia in 7-40 times. There are considerable territorial disparities of net costs of heating generation too. The settlements of Yakutia are not compact, have a large area because of the specific agricultural specialization. Construction of new buildings of public services increases the number of low-capacity boilers. There are 1355 heating units operating in villages and cities of Yakutia. The share of houses with central heating varies greatly. In settlements with significant proportion of houses with stove heating there is a reduction in forest area within a radius of 20-40 km, which leads to an increase in environmental problems. Yakutia obtains a certain effect from programs of local energy optimization systems and implementation of energy saving measures, including gasification of settlements, but budget costs are still very significant. This is a common problem for all northern countries. At present the system of cross-subsidization of energy consumption changes. It meant that a part of the energy consumption costs of economic agents have been paid by other economic agents, including the state. Its main reason is population poverty. Actually Inhabitants compensate by own funds only 25.5% of the real cost of central heating, 78.2% - of electricity. It is considerably lower than in Russia in general. The transition to rates, based on real costs, will lead to a rapid loss of population in the Arctic and other remote areas. At the same time the crisis in Russia dictates the necessity of reform of the energy sector, in particular by reducing energy consumption. Some programs envisage the improvement of urban planning, concentration and increase in the density of population in large settlements and towns of Yakutia. Concentration allows to get a significant saving in energy costs, however it leads to an increase in the anthropogenic impact on the environment. Areas, where the largest power plants are located, provide the highest CO2 emission. These are Serebryany Bor (Neryungri district), Yakutsk and Svetly (Mirninsky district). These settlements are the centers of intensive anthropogenic impact on the environment by energy generation activity. The reform of energy system in Yakutia is complicated. It is closely related to the transformation of the spatial structure. Liquidation of the Arctic settlements is objectively impossible due to national security interests, historical and cultural traditions of indigenous peoples that we have to protect. The searching for new technological, spatial, financial and social mechanisms for wellbeing of northern communities is needed. Republic of Sakha (Yakutia) needs a new spatial structure. Moreover, it can be fundamentally new. For example, decentralized, allowing disperse anthropogenic load on the environment, if in the near future, new technologies will provide individual livelihoods and access to basic social services to households in rural areas. Alternatively, it could be more concentrated, not linear-focal and linear as now. When large urban settlements will be located on the main highways or rivers. This problem can be solved in the framework of strategic planning in the region. Continuing of studies of transport isolation, market and economic potential of northern communities are needed.
Keywords: Q28; Q41; Q56; R32; 330; North; energy system; net cost; energy consumption; heat energy; cross-subsidization; Arctic settlements; population; territorial disparities